Increased survival associated with surgery and radiation therapy in metastatic gastric cancer. Issue 9 (29th January 2013) - Shridhar, Ravi; Almhanna, Khaldoun; Hoffe, Sarah E.; Fulp, William; Weber, Jill; Chuong, Michael D.; Meredith, Kenneth L.
Abstract BACKGROUND: Patients with metastatic gastric cancer have poor survival. The purpose of this study was to compare outcomes of metastatic gastric cancer patients stratified by surgery and radiation therapy. METHODS: The Surveillance, Epidemiology, and End Results (SEER) database was accessed to identify patients with AJCC M1 stage IV gastric cancer (based on the American Joint Committee on Cancer Cancer Staging Manual, 6th edition) between 2004 thru 2008. Patients were divided into 4 groups: group 1, no surgery or radiation; group 2, radiation alone; group 3, surgery alone; group 4, surgery and radiation. Survival analysis was determined by Kaplan‐Meier and log‐rank analysis. Multivariate analysis (MVA) was analyzed by the Cox proportional hazard ratio model. RESULTS: A total of 5072 patients were identified. Surgery and/or radiation were associated with a survival benefit. Median and 2‐year survival for groups 1, 2, 3, and 4 was 7 months and 8.2%, 8 months and 8.9%, 10 months and 18.2%, and 16 months and 31.7%, respectively (P < .00001). MVA for all patients revealed that surgery and radiation were associated with decreased mortality whereas T‐stage, N‐stage, age, signet ring histology, and peritoneal metastases were associated with increased mortality. In patients treated with surgery, MVA showed that radiation was associated with decreased mortality, whereas T‐stage, N‐stage, age, removal of < 15 lymph nodes, signet ring histology, and peritoneal metastases was associated with increased mortality. Age was the only prognostic factor in patients who did not undergo surgery. CONCLUSIONS: Surgery and radiation are associated with increased survival in a subset of patients with metastatic gastric cancer. Prospective trials will be needed to address the role and sequence of surgery and radiation in metastatic gastric cancer. Cancer 2013. © 2013 American Cancer Society.